Socio-demographic factors and children's independent mobility: A comparative analysis of discretionary and non-discretionary trips - Rufia Andisetyana Putri; Imam Buchori; Anang Wahyu Sejati; Apin Fitri Amalina (Regional Development Information Center, Universitas Sebelas Maret, 2026)
Children's independent mobility (CIM) has declined in recent decades, affecting not only non-discretionary trips but also discretionary trips undertaken for leisure purposes. This trend may have implications for children's development and environmental sustainability. At the same time, neighbourhood resilience can be enhanced through the provision of neighbourhood-scale facilities that support children's daily mobility and independent travel. This study aims to compare children's independent mobility in discretionary and non-discretionary trips based on socio-demographic characteristics. The study was conducted in Perumnas Krapyak, Semarang City, Indonesia, and focused on children aged 7–12 years. The research area was delineated using GIS-based analysis according to children's walking-distance capabilities. Data were collected through questionnaires administered to 30 children equally distributed by age and gender and analysed descriptively. The results show that children's independent mobility was higher in discretionary trips (70%; CIM Level 3) than in non-discretionary trips (51.11%; CIM Level 2). Higher levels of independent mobility were associated with older age, male gender, peer presence, bicycle ownership, and familiarity with neighbours. These findings suggest that neighbourhood characteristics and socio-demographic factors play an important role in supporting children's independent mobility and contribute to the development of more child-friendly and resilient neighbourhoods.